2021
DOI: 10.3390/en14061692
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Study on the Shear Strength Behavior of Two Till Deposits from Northern Germany

Abstract: This paper presents the findings of a laboratory study of the shear strength and yielding behavior of two glacial till soil deposits from the area of Heiligenhafen, northern Germany. The tests were conducted on reconstituted forms of the soils using a triaxial cell capable of controlling the temperature of the specimens. The experimental program included a series of multi-stage consolidated drained (CD) compression triaxial tests at temperature ranges between 20 and 60 °C. For the temperature range considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The minor initial contraction of the soil exhibited at the beginning of the test which was followed by a dilation of an almost equal magnitude is what one would expect for a normally consolidated soil with moderate density. This is also corroborated by the findings of previous studies, which showed that dense overconsolidated soils tend to dilate strongly upon shearing while loose normally consolidated soils tend to compress strongly when sheared [20,21].…”
Section: Shearing or Deformation Phase Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The minor initial contraction of the soil exhibited at the beginning of the test which was followed by a dilation of an almost equal magnitude is what one would expect for a normally consolidated soil with moderate density. This is also corroborated by the findings of previous studies, which showed that dense overconsolidated soils tend to dilate strongly upon shearing while loose normally consolidated soils tend to compress strongly when sheared [20,21].…”
Section: Shearing or Deformation Phase Resultssupporting
confidence: 88%
“…Previous studies [1,8,21] indicated that when heated to high temperature states, overconsolidated soils with high density generally exhibit a thermal expansive or dilatant behavior, thus losing shear strength, whereas normally consolidated or loose soils with a relatively low density exhibit a thermal compaction or contractive behavior when heated, thus gaining shear strength, due to the creation of a more compact soil volume after grain restructuring in the soil skeleton due to the heating process. Considering the above factors and the moderate initial density of the silty clay soil used in this research, the results (i.e., negligible changes in shear strength of soil after heating) presented in this study corroborate these previous findings.…”
Section: Shearing or Deformation Phase Resultsmentioning
confidence: 99%
“…Secondly, the shear strength of glacial deposits in the uppermost layer of the Ludoialm landslide is relatively low. The friction angle of about 19 • is smaller than that of the glacial till in most cases, which is around 30 • , or at least larger than 20 • [89][90][91][92][93]. This weak material fosters the instability of the slope, which was reactivated twice in the past decades even though the slope is quite gentle with the dip angle smaller than the soil friction angle of the sliding mass.…”
Section: Unique Geological Situationmentioning
confidence: 93%
“…Two naturally occurring glacial tills from the 'Hohe Ufer' cliff, found in the Heiligenhafen area of Schleswig-Holstein, northern Germany [25,26], were used for the study (Figures 1 and 2). As reported in Hailemariam and Wuttke [26], the two glacial tills are also labeled here in this study as 'oM' or "oberer Geschiebemergel" for the upper or younger Weichselian till deposit collected from site 1, and as 'mM' or "mittlerer Geschiebemergel" for the middle or comparatively older Saalian till deposit collected from site 2 (see Figure 1).…”
Section: Experimental Program 21 Tested Glacial Till Depositsmentioning
confidence: 99%